Biventricular dysfunction predicts mortality in ST elevation myocardial infarction patients with cardiogenic shock - Angga Dwi Prasetyo; Hendry Purnasidha Bagaswoto; Firandi Saputra; Erika Maharani; Budi Yuli Setianto (The Egyptian Heart Journal)
Abstract Background The incidence of mortality in patients with cardiogenic shock due to ST elevation myocardial infarction (STEMI) remains high even with prompt reperfusion therapy. Ventricular systolic dysfunction is the primary condition causing cardiogenic shock in STEMI. Studies have been widely conducted on the left ventricle (LV) and right ventricle (RV) systolic dysfunction related to mortality events. However, the parameters of biventricular systolic dysfunction predicting mortality as a stronger predictor of mortality are still unclear. Accordingly, we evaluated the predictor mortality value of biventricular systolic dysfunction in STEMI patients with cardiogenic shocks. Based on The Society for Cardiovascular Angiography and Intervention classification, we analyzed data from November 2021 to September 2023 at Dr. Sardjito General Hospital in Yogyakarta, Indonesia, using the Sardjito Cardiovascular Intensive Care (SCIENCE) registry with a retrospective cohort design. Multivariate logistic regression analysis was used to assess predictors of in-hospital mortality. Results There were 1,059 subjects with a mean ± SD age of 59 ± 11 years, dominated by men (80.5%) who met the inclusion and exclusion criteria. Based on multivariate analysis, biventricular dysfunction (BVD) is a factor that significantly increases the risk of in-hospital mortality (Odds ratio [OR], 1.771: 95% confidence interval [CI] 1.113–2.819; p = 0.016). Other significant factors affecting mortality were renal failure (OR, 5.122; 95% CI 3.233–8.116; p < 0.001), percutaneous coronary intervention (PCI) (OR, 0.493; 95% CI 0.248–0.981; p = 0.044), and inotropic/vasopressor (OR, 6.876; 95% CI 4.583–10.315; p < 0.001). Conclusions Biventricular dysfunction significantly increases the risk of in-hospital mortality in STEMI patients with cardiogenic shock. Renal failure, PCI, and the requirement for inotropic or vasopressor drugs are also factors that influence in-hospital mortality.